2022
DOI: 10.1007/s00428-021-03238-8
|View full text |Cite
|
Sign up to set email alerts
|

BCL3 expression is strongly associated with the occurrence of breast cancer relapse under tamoxifen treatment in a retrospective cohort study

Abstract: Patients with estrogen receptor positive breast cancer are usually receiving an anti-estrogen therapy by either aromatase inhibitors or selective estrogen receptor mediators such as tamoxifen. Nevertheless, acquired resistance to tamoxifen under treatment frequently hampers therapy. One proposed explanation for this phenomenon is the interaction of the tumor cells with cells of the tumor microenvironment via the Insulin-like growth factor RNA binding protein 5/B-cell lymphoma 3 (IGFBP5/BCL3) axis. Here we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…In these pathways, the NF-kB-inhibitor α (NFKBIA) represented one of the major hits. This is consistent with the data suggesting that NF-kB plays an important role in acquired tamoxifen resistance [ 52 , 53 , 54 , 55 , 56 ]. The result for the pathway leading to morphine addiction seems hard to explain; however, several effects of tamoxifen on morphine responses and vice versa have been published.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In these pathways, the NF-kB-inhibitor α (NFKBIA) represented one of the major hits. This is consistent with the data suggesting that NF-kB plays an important role in acquired tamoxifen resistance [ 52 , 53 , 54 , 55 , 56 ]. The result for the pathway leading to morphine addiction seems hard to explain; however, several effects of tamoxifen on morphine responses and vice versa have been published.…”
Section: Discussionsupporting
confidence: 93%
“…DOCK-AS2 was indeed moderately up-regulated in MCF-7 by 4OH tamoxifen (log 2 Fc = 0.5, p adj = 0.007); however, CTNNB1 was not. Interestingly, in thyroid cancer, this DOCK2-AS2 sponging was correlated with WNT-signalling, a pathway that is also supposed to be involved in tamoxifen resistance [ 56 , 74 , 75 ]. Nevertheless, possible sponging mechanisms on miR-1972 require further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, analysis of the role of the unique genes in MCF7-ERβ1 cells revealed that the regulation of all but one of the hub genes (PPARG, HIPK2, ZFP36L1, HMGB2 and ALDH1A3) and of 12 more unique genes (ASCL1, ID3, GPNMB, SGK3, BAG3, WDR73, ALKBH1, HIGD1A, FGD3, ACAA2, DOCK8 and AGR3) reportedly favors inhibition of breast cancer cell proliferation and tumorigenicity, induction of cell death and/or better clinical outcome [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. In contrast, in ERβ2-expressing cells, the regulation of the two unique hub genes (CXCL12 and SIX4) and of nine of the other unique genes (INHBE, GADD45B, RPS7, IFIT3, IGFBP3, JAG2, BCL3, GPR37L1 and KRT80) reportedly favors inhibition of cell death, resistance of BC to endocrine therapy and poor clinical prognosis [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. Indicative functions reported for all cell-death-related genes uniquely regulated in MCF7-WT, MCF7-ERβ1 and MCF7-ERβ2 cells are presented in Supplementary Tables S10–S12 .…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, the rise in CAIX expression in CAF-CM-treated cells is not linked to TIMP-1. We have previously shown by using MCF-7 cells that CAF-CM upregulates CAIX expression through a CAF-CM-induced increase in the expression of Bcl-3 [ 30 ], a IκB-like protein involved in anti-estrogen resistance [ 49 ]. CAIX has also been shown to play a role in drug resistance [ 47 ].…”
Section: Discussionmentioning
confidence: 99%